Effect of Helichrysum italicum on the corrosion of copper in simulated acid rain solution - Pilić, Zora (Array, 2020)
The inhibition of copper corrosion by Helichrysum italicum extract (HI) in simulated acid rain was investigated using electrochemical techniques. Results indicate an increase in corrosion inhibition efficiency with the HI extract concentration. The inhibitive process was assumed to occur via adsorption of the extract on the metal surface. The thermodynamic data indicated physical adsorption and followed the Freundlich isotherm. The effect of temperature on the copper corrosion was studied. The value of the activation energy confirmed physisorption of extract molecules on the copper surface. The concentration of Cu ions released into solution, measured by atomic absorption spectrometry, was in accordance with the electrochemical results.